2015
DOI: 10.1002/mus.24478
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome severity staging using sonographic and clinical measures

Abstract: Introduction Ultrasonography may be valuable in staging carpal tunnel syndrome severity, especially by combining multiple measures. This study aimed to develop a preliminary severity staging model using multiple sonographic and clinical measures. Methods Measures were obtained in 104 participants. Multiple categorization structures for each variable were correlated to diagnostic severity based on nerve conduction. Goodness-of-fit was evaluated for models using iterative combinations of highly correlated vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…The mean cross‐sectional area values were smallest in group 1. These results are in accordance with many previous studies reporting that abnormal nerve function in various pathologic conditions is correlated with nerve cross‐sectional area enlargement . Our results are also consistent with a few previous reports describing sonographic findings and their correlations with pathophysiologic types .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The mean cross‐sectional area values were smallest in group 1. These results are in accordance with many previous studies reporting that abnormal nerve function in various pathologic conditions is correlated with nerve cross‐sectional area enlargement . Our results are also consistent with a few previous reports describing sonographic findings and their correlations with pathophysiologic types .…”
Section: Discussionsupporting
confidence: 94%
“…These results are in accordance with many previous studies reporting that abnormal nerve function in various pathologic conditions is correlated with nerve cross-sectional area enlargement. 4,15 Our results are also consistent with a few previous reports describing sonographic findings and their correlations with pathophysiologic types. 9,10 Several studies have reported that axonal nerve lesions lead to greater nerve swelling than demyelinating lesions do.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent study by Roll et al used a similar multicomponent approach to develop a scoring system for grading the severity of CTS, which also incorporated the Boston Carpal Tunnel Questionnaire grade and provocative tests, as well as nerve vascularity and longitudinal irregularity, but complex US parameters were not addressed in that study. Considering observed variations in the site of median nerve enlargement and an increase in the sensitivity of the mean cross‐sectional area compared to the inlet cross‐sectional area, we propose measuring inlet and outlet cross‐sectional areas for inlet‐outlet mean cross‐sectional area calculation, as well as the forearm cross‐sectional area, because of the correlation of the wrist‐to‐forearm ratio with clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additional findings reported through MUS, such as the echogenicity of the median nerve, its mobility, or an edema of the flexor retinaculum, may also aid in the diagnosis of CTS. The sonographic findings in patients suffering from CTS include median nerve swelling, compression of the nerve, palmar migration, and thickening of the flexor retinaculum, along with changes in the characteristic features of the median nerve [8-10].…”
Section: Reviewmentioning
confidence: 99%